Quantitative 3D-KPFM imaging with simultaneous electrostatic force and force gradient detection. (8th April 2015) - Collins, L; Okatan, M B; Li, Q; Kravenchenko, I I; Lavrik, N V; Kalinin, S V; Rodriguez, B J; Jesse, S
Abstract: Kelvin probe force microscopy (KPFM) is a powerful characterization technique for imaging local electrochemical and electrostatic potential distributions and has been applied across a broad range of materials and devices. Proper interpretation of the local KPFM data can be complicated, however, by convolution of the true surface potential under the tip with additional contributions due to long range capacitive coupling between the probe (e.g. cantilever, cone, tip apex) and the sample under test. In this work, band excitation (BE)-KPFM is used to negate such effects. In contrast to traditional single frequency KPFM, multifrequency BE-KPFM is shown to afford dual sensitivity to both the electrostatic force and the force gradient detection, analogous to simultaneous amplitude modulated and frequency modulated KPFM imaging. BE-KPFM is demonstrated on a Pt/Au/SiO x test structure and electrostatic force gradient detection is found to lead to an improved lateral resolution compared to electrostatic force detection. Finally, a 3D-KPFM imaging technique is developed. Force volume (FV) BE-KPFM allows the tip–sample distance dependence of the electrostatic interactions (force and force gradient) to be recorded at each point across the sample surface. As such, FVBE-KPFM provides a much needed pathway towards complete tip–sample capacitive de-convolution in KPFM measurements and will enable quantitative surface potential measurements with nanoscale resolution.